Three‐dimensional echocardiography in the evaluation and management of paravalvular regurgitation. Issue 12 (15th November 2018) - Kinno, Menhel; Raissi, Sasan R.; Olson, Kristoff A.; Rigolin, Vera H.
Abstract: Paravalvular regurgitation is an uncommon but serious complication that can be encountered after either surgical or percutaneous valve replacement and is associated with increased morbidity and mortality. Early detection and accurate assessment of paravalvular regurgitation are crucial to identify those who would benefit from intervention. Recent advances in 3‐dimensional echocardiography have increased the feasibility of percutaneous approaches for the management of paravalvular regurgitation. Percutaneous closure of paravalvular regurgitation has emerged as a favorable alternative for redo surgery in selected cases. This article will review the role of 3‐dimensional echocardiography in the assessment and management of paravalvular regurgitation.